Calibration of three-dimensional model PCFLOW3D - a comparison with measurements from the Yatsushiro Sea and the Sea of Japan - Rajar, Rudolf (Acta hydrotechnica, 2017)
PCFLOW3D is a three-dimensional numerical model that simulates the hydrodynamic circulation and transport/dispersion of various pollutants. As the first hydrodynamic (HD) part is crucial for the reliable simulation of further transport/dispersion processes, we have been diligently developing it for several years, calibrating and verifying it at every stage of development. This paper presents two cases where it was possible to draw a comparison with current measurements or observations, and describes several improvements to the model that proved necessary in order to simulate the desired range of complex hydrodynamic situations. In the first case (Case A) we made good use of the available, quite detailed measurements of currents in the Yatsushiro Sea (Japan). Due to the very high and variable current velocities we had to include a better turbulence model (Smagorinsky) to get acceptable agreement with the measurements. In the second case (Case B) we simulated HD circulation in the Sea of Japan, where thermohaline forcing is very important; this called for the model to be completed with a special term, namely so-called topographic stress. In both cases the final agreement is good; in Case B we also describe the simulation of the transport/dispersion of radioactive pollutants in the Sea of Japan.
Keywords: current measurements; Japonsko morje; meritve tokov; morje Yatsushiro; radioactive pollution; radioaktivna onesnažila; Sea of Japan; three-dimensional numerical model; tridimenzionalni numerični hidrodinamični model; Yatsushiro Sea